The Savior Image in Online Collaborative Learning: How Adult Learning Groups Manage Age-related Difference - Regina O. Smith; John M. Dirkx (Adult Education Research Conference, 2006)
This qualitative cross-case study examines how age-related differences are manifest and managed within online groups of adult learners. The findings suggest lack of traditional instruction in the PBL groups created a vacuum of authority, which they were unable to satisfactorily resolve.
Keywords: Collaborative learning; mixed-age groups; psychodynamics learning theory